ERIC and WGS Typing of Paenibacillus larvae in Slovenia: Investigation of ERIC I Outbreaks - Alenka Žugelj; Bojan Papić; Irena Zdovc; Urška Zajc; Majda Golob; Jana Avberšek; Darja Kušar (Insects, 2021)
Paenibacillus larvae is the causative agent of American foulbrood (AFB), a fatal disease of honeybee brood. Here, we obtained 506 P. larvae isolates originating from honey or brood samples and from different geographic regions of Slovenia in the period 2017–2019. In the first part of the study, we conducted ERIC-PCR typing to assess the frequency of ERIC types in Slovenia. Capillary electrophoresis was used for the analysis of ERIC patterns, revealing good separation efficiency and enabling easy lane-to-lane comparisons. ERIC II was the predominant type (70.2%), followed by ERIC I (29.8%); two slightly altered ERIC I banding patterns were observed but were not considered relevant for the discrimination of ERIC types. No evident spatiotemporal clustering of ERIC types was observed. To assess the clonality of the outbreak-related P. larvae ERIC I isolates, 59 isolates of this type underwent whole-genome sequencing (WGS). Whole-genome multilocus sequence typing (wgMLST) revealed seven ERIC I-ST2 outbreak clusters (≤35 allele differences) with the median intra-outbreak diversity ranging from 7 to 27 allele differences. In all seven clusters, the transmission of P. larvae outbreak clone within a 3-km radius (AFB zone) was observed, which could be explained by the activity of honeybees. In three clusters, the transmission of the outbreak clone between geographically distant apiaries was revealed, which could be explained by the activities of beekeepers such as migratory beekeeping and trading of bee colonies. The present findings reinforce the importance of beekeeping activities in the transmission of P. larvae. WGS should be used as a reference typing method for the detection of P. larvae transmission clusters.